Impact of carbohydrate nutrition on exercise metabolism and performance - Newell, M. L.; Wallis, G. A.; Galloway, S. D. R. (Agro Food Industrial Hi Tech, 2014)
Carbohydrate (CHO) ingestion before and during exercise has consistently been reported to increase endurance exercise capacity/performance but the mechanisms responsible and optimal dose required are still debated. Feeding CHO is believed to spare muscle glycogen, spare liver glycogen, have central neural actions, and peripheral neural effects. A combination of these mechanisms is likely and the nature of the exercise performed is key when interpreting these data. Research on the optimal dose of CHO to improve performance over a range of exercise durations and intensities has been a recent focus. Optimal doses suggested from these studies cover a range (30-80 g•h-1) that likely reflects exercise task, training status, and/or individual variation in response